WORK AND RECOVERY: FROM POLICIES TO INDIVIDUALS - Mezzina, Roberto; Marin, Izabel (Brazilian Journal of Mental Health, 2021)
The current international context of vocational rehabilitation and job placement includes health and legal implications, encompassing WHO documents, the research on social determinants of health, the UN Sustainable Development Goals (SDGs), the Convention on the Rights of Persons with Disabilities, State policies. The social enterprise is described as a universe of organizations based on the primacy of people over capital, which includes organizational forms such as cooperatives, foundations and associations. It is aimed at bridging the gap between welfare and productive worlds and at enhancing the potential of service users and other citizens with disabilities or social disadvantage toward emancipation. Italian laws provided a framework for this development of “real work for a real pay” and especially Trieste is an example of integration of social cooperatives in the rehabilitation and social inclusion strategies of mental health. Among available quantitative research data, qualitative research based on first person’s accounts focuses on the role of work opportunities in the recovery process and provides a more nuanced view. Work can be stressful at times, but it anchors the individual to reality and provides social inclusion per se. The prospect of a wider approach, as the one offered by social enterprise, with its social values linked to a different kind of employment, confirms those individual perspectives, while it combines community engagement and coproduction.